Osteoclast-Derived Extracellular Vesicles: Novel Regulators of Osteoclastogenesis and Osteoclast–Osteoblasts Communication in Bone Remodeling - Yuan, Feng-Lai; Wu, Qian-yuan; Miao, Zong-Ning; Xu, Ming-Hui; Xu, Rui-Sheng; Jiang, Dong-Lin; Ye, Jun-Xing; Chen, Fei-hu; Zhao, Ming-Dong; Wang, Hao-jue; Li, Xia (Frontiers in Physiology, 2018)
Extracellular vesicles (EVs), including exosomes, microvesicles and apoptotic bodies, play an important role in cellular communication during skeletal growth and homeostasis. Bioactive molecules carried by EVs are transported to neighboring and distant cells to trigger a series of signaling cascades influencing bone homeostasis. The bioactive activities of osteoclast-derived EVs include regulation of osteoclastogenesis and osteoclast-osteoblast communication. As osteoclast-derived EVs have the potential to regulate osteoclasts and osteoblasts, their application in osteoporosis and other bone metabolic disorders is currently under investigation. However, very few reviews of osteoclast-derived EVs in bone remodeling regulation have yet been published. This article aims to review recent advances in this field, summarizing the underlying molecular mechanisms by which osteoclast-derived EVs influence osteoclastogenesis and osteoclast-osteoblast communication. We will analyze the major challenges in the field and potential for the therapeutic application of EVs.